1963
DOI: 10.1001/archderm.1963.01590200064012
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Erythematosus and Erythema Multiforme-like Lesions

Abstract: erythema multiforme-like (EM) lesions, positive speckled ANA, RF and Anti-SJT antibody, later known as anti Ro/La antibodies. In 2000, Zeitouni et al extended the definition by including all types of systemic lupus erythematosus (SLE) and proposed major and minor criteria, while in 2012 Torchia et al proposed another set of criteria defining Rowell syndrome as a distinct subtype of chronic cutaneous lupus. To date, Rowell syndrome as a distinct entity remains in question. Objectives: To establish whether patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
99
0
2

Year Published

1967
1967
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 209 publications
(109 citation statements)
references
References 8 publications
8
99
0
2
Order By: Relevance
“…2003;139:45-49 S UBSETS OF cutaneous lupus erythematosus (CLE ) associated with the presence of anti-Ro/SSA antibodies include the following [1][2][3][4][5][6][7][8][9] : (1) drug-induced lupus erythematosus (LE); (2) neonatal LE; (3) LE with inherited C2 and C4 deformities; (4) LE in the elderly; (5) Sjö gren syndrome; (6) LE and benign hypergammaglobulinemic purpura of Waldenstrom syndrome (lymphocytic vasculitis); (7) LE and photosensitivity; (8) subacute CLE (SCLE); and (9) LE with erythema multiformelike lesions (Rowell syndrome). The most recent and least characterized subset of LE has been the phenomenon of drug-induced Ro/SSApositive CLE.…”
Section: Discussionmentioning
confidence: 99%
“…2003;139:45-49 S UBSETS OF cutaneous lupus erythematosus (CLE ) associated with the presence of anti-Ro/SSA antibodies include the following [1][2][3][4][5][6][7][8][9] : (1) drug-induced lupus erythematosus (LE); (2) neonatal LE; (3) LE with inherited C2 and C4 deformities; (4) LE in the elderly; (5) Sjö gren syndrome; (6) LE and benign hypergammaglobulinemic purpura of Waldenstrom syndrome (lymphocytic vasculitis); (7) LE and photosensitivity; (8) subacute CLE (SCLE); and (9) LE with erythema multiformelike lesions (Rowell syndrome). The most recent and least characterized subset of LE has been the phenomenon of drug-induced Ro/SSApositive CLE.…”
Section: Discussionmentioning
confidence: 99%
“…In 1963, Rowell et al reported a unique syndrome characterized by SLE, EM-like lesions, a positive test for RF, speckled ANA and a saline extract of human tissue (anti-SJT) which is now known as similar to Ro (SSA) [1]. Since the first report of Rowell's syndrome very few cases have been reported in the literature in which the presence of EM-like lesions are associated with LE.…”
Section: Discussionmentioning
confidence: 99%
“…In 1963, Rowell defined this association as a distinct entity upon discovering different clinical and immunologic findings in four patient during his study including 120 discoid lupus erythematosus (DLE) patients. The original criteria of Rowell's syndrome comprised of LE, EM like lesions and immunological abnormalities such as speckled pattern of ANA, RF and saline extract of human tissue (anti-SJT) positivity which is now regarded as similar to anti-Ro [1]. Although this syndrome was originally described in DLE patients, some of these patients developed SLE years after the onset of DLE [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations